ADAPTASI KONSEP PURUSA-PRAKERTI PADA PURA DANG KAHYANGAN KAPRUSAN DAN BATU BOLONG DI BATU LAYAR LOMBOK BARAT - Dewi Rahayu Aryaningsih; Ni Made Ria Taurisia Armayani; Ida Ayu Widia Laksmi; Gde Eka Puja Diatmika (Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
This study aims to conduct a study of the adaptation of the purusa-prakerti concept at the Pura Dang Kahyangan, namely Kaprusan and Batu Bolong in Batu Layar District, West Lombok Regency. This study was designed as a qualitative descriptive study in order to describe the concept of purusa-prakerti adapted in Hindu religious temple at Kaprusan and Batu Bolong. Data were collected through observation, interviews and document analysis. This study found that Dang Hyang Nirartha's journey in Lombok built a number of temples as a place to do yoga which is still used as a place to carry out Hindu religious activities. Kaprusan Temple and Batu Bolong Temple are two temples where yoga practice has a special identity, namely adaptation to the purusa-prakerti concept taught in the samkhya darsana system. The Kaprusan temple is cosmologically related to the presence of a burst of sea water hitting the walls of the rock cave which is termed kaprusan as a representation of the phallus (masculine). The phonological dimension gives the meaning of